THE EFFECT OF SMALL GROUP DISCUSSION TEACHING METHOD TO THE READING COMPREHENSION OF GRADE EIGHT STUDENTS OF SMP NEGERI 4 PEMATANG SIANTAR ON A DESCRIPTIVE TEXT - Widya Ambarita; Sanggam Siahaan; Bloner Sinurat (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose of this study is to find out whether the effect of small group discussion teaching method to the reading comprehension of grade eight students of SMP Negeri 4 Pematang Siantar. This research uses quantitative research with a quasi-experimental research methodology. Creswell (2012:27),explains that